Revitalizing Examination Systems in Nepalese Universities: A Case Study of Tribhuvan University, Kathmandu - Adhikary, Ramesh Prasad; Acharya, Tank Prasad (Academia Research Journal, 2026)
Tribhuvan University (TU), the largest and oldest institution of higher education in Nepal, has a centralized, manual system of examinations characterized by systemic inefficiencies: a delay of over 12-19 months in results publication, which exists for bachelor level students enrolled in the annual system, political interference in the selection of examiners, the potential insecurity in the handling of answer sheets and predominant validity of examinations based on rote learning that suffers from an insincere evaluation in measurement of critical thinking and practical skills. These deficiencies, in turn, lead to extended program completion, loss of assessment validity, loss of stakeholder trust and graduate employability which go against commitments of Sustainable Development Goal 4 and the National Education Policy (2022) of Nepal on quality and equity. This sequential explanatory mixed methods research study evaluated the system against a global bench mark and proposed a reform. Quantitative data on a total of 395 respondents (217 students, 118 faculty and 60 administrative staff) using a valid survey identified deep dissatisfaction of the respondents' with low mean score obtained on efficiency (M=2.12, SD=0.95), transparency (M=2. 05, SD=0.91), security (M= 1.91, SD=0.89), fairness (M=2.28, SD=1.02) and timeliness (M=1.62, SD=0 Five core barriers that foreseeably arise from processing bottlenecks from centralization, biased influences, inadequate safeguards, rote-dominant evaluation, and regional inequities were identified through thematic analysis of 25 semi-structured interviews. Anchored in Institutional Theory, Systems Theory and the Technology Acceptance Model results in a high level of consensus for reform (digital support M = 4.38; regional centers M = 4.25), indicating a high level of perceived usefulness. The proposed framework combines autonomous regional centers, secure digital platforms, competency-based assessment, and independent oversight to create greater efficiency, transparency and integrity which provides a replicable model when resources are mated with resource constrained systems.